Influence of alternative photoinitiators in composite resins: A literature review (Research, Society and Development, 2020)
Objective: To evaluate the influence of alternative photoinitiators present in composite resins related to yellowing, color stability, photosensitivity, light-curing efficiency, degree of conversion, and microhardness. Materials and methods: The literature was reviewed by two independent reviewers at PubMed. The search strategy was carried out using the following descriptors: (Photoinitiators, dental) AND (Curing lights, dental) AND (Composite Resins) NOT (Case report). The electronic search was carried out until March 2019, without language restrictions, and inclusion and exclusion criteria were applied in the selection. Results: Thirteen articles met the previously established criteria, and all were included. Of these, most were in vitro studies. After the aging of the composite, all systems suffered yellowing, however the isolates with camphorquinone were the most affected and, although there is a greater tendency to yellowing, this does not directly affect color stability. However, the literature is still conflicting about which system has significant color stability. Regarding photosensitivity, all photoinitiators have different absorption peaks. In this sense, the photopolymerization must be chosen with caution, as the conversion of monomers and microhardness proved to be directly linked to the correct combination of photoactivator and photopolymerizing unit. Conclusion: Alternative photoinitiators have a lower yellowing rate and good color stability. They can be up to five times more sensitive than systems containing isolated camphorquinone. Only third-generation light-emitting diodes photopolymerize satisfactorily composite resins that have alternative photoinitiators in their composition, ensuring a good degree of conversion and acceptable Knoop microhardness values.